Echocardiographic assessment of conjoined twins. Issue 3 (23rd August 2005) - Andrews, R E; McMahon, C J; Yates, R W M; Cullen, S; de Leval, M R; Kiely, E M; Spitz, L; Sullivan, I D
Abstract : Objective: To determine the accuracy of prenatal and postnatal echocardiography in delineating the degree of cardiac fusion, intracardiac anatomy (ICA), and ventricular function of 23 sets of conjoined twins with thoracic level fusion presenting to a single centre over a 20 year period. Methods: 13 thoracopagus, 5 thoraco-omphalopagus, and 5 parapagus pairs presenting to the authors' institution between 1985 and 2004 inclusive were assessed. Echocardiographic data were analysed together with operative intervention and outcome. Twins were classified according to the degree of cardiac fusion: separate hearts and pericardium (group A, n = 5), separate hearts and common pericardium (group B, n = 7), fused atria and separate ventricles (group C, n = 2), and fused atria and ventricles (group D, n = 9). Results: The degree of cardiac fusion was correctly diagnosed in all but one set. ICA was correctly diagnosed in all cases, although the antenatal diagnosis was revised postnatally in three cases. Abnormal ICA was found in one twin only in two group A pairs, one group B pair, and both group C pairs. All group D twins had abnormal anatomy. Ventricular function was good in all twins scanned prenatally, and postnatally function correlated well with clinical condition. Thirteen sets of twins in groups A–C were surgically separated; 16 of 26 survived. None from groups C or D survived. Conclusions: Prenatal and postnatal echocardiography accurately delineates cardiac fusion, ICA, and ventricular function in the majority of twins with thoracic level fusion. It is integral in assessing feasibility of separation. The outcome in twins with fused hearts remains dismal.